Charge transport in nanoparticular thin films of zinc oxide and aluminum-doped zinc oxide - Lenz, Thomas; Richter, Moses; Matt, Gebhard; Luechinger, N.A.; Halim, S.C.; Heiß, Wolfgang; Brabec, Christoph (Journal of Materials Chemistry C, 2015)
In this work, we report on the electrical characterization of nanoparticular thin films of zinc oxide (ZnO) and aluminum-doped ZnO (AZO). Temperature-dependent current-voltage measurements revealed that charge transport for both, ZnO and AZO, is well described by the Poole-Frenkel model and excellent agreement between the experimental data and the theoretical predictions is demonstrated. For the first time it is shown that the nature of the charge-transport is not affected by the doping of the nanoparticles and it is proposed that the Poole-Frenkel effect is an intrinsic and universally limiting mechanism for the charge transport in nanoparticular thin films with defect states within the bandgap. © The Royal Society of Chemistry 2015.
Keywords: Engineering controlled terms: Aluminum; Carrier transport; Optical films; Semiconductor doping; Thin films; Zinc; Zinc oxide Aluminum-doped zinc oxide; Aluminum-doped ZnO; Current voltage measurement; Electrical characterization; Poole-Frenkel effect; Poole-Frenkel model; Temperature dependent; Zinc oxide (ZnO) Engineering main heading: Oxide films

Phosphonate- and Carboxylate-Based Self-Assembled Monolayers for Organic Devices: A Theoretical Study of Surface Binding on Aluminum Oxide with Experimental Support - Bauer, Thilo; Schmaltz, Thomas; Lenz, Thomas; Halik, Marcus; Meyer, Bernd; Clark, Timothy (ACS Applied Materials and Interfaces, 2013)
We report a computational study on the chemical bonding of phosphonates and carboxylates to aluminum oxide surfaces and how the binding properties are related to the amount of water in the experimental environment. Two different surface structures were used in the calculations in order to model representative adsorption sites for the phosphonates and carboxylates and to account for the amorphous nature of the hydroxylated AlOx films in experiment. For the phosphonates, we find that the thermodynamically preferred binding mode changes between mono-, bi-, and tridentate depending on the surface structure and the amount of residual water. For the carboxylates, on the other hand, monodentate adsorption is always lower in energy at all experimental conditions. Phosphonates are more strongly bound to aluminum oxide than carboxylates, so that carboxylates can be replaced easily by phosphonates. The theoretical findings are consistent with those obtained in adsorption, desorption, and exchange reactions of n-alkyl phosphonic and carboxylic acids on AlOx surfaces. The results provide an atomistic understanding of the adsorption and help to optimize experimental conditions for self-assembly of organic films on aluminum oxide surfaces.

Self-Assembled Monolayer Exchange Reactions as a Tool for Channel Interface Engineering in Low-Voltage Organic Thin-Film Transistors - Lenz, Thomas; Schmaltz, Thomas; Novak, Michael; Halik, Marcus (Langmuir, 2012)
In this work, we compared the kinetics of monolayer self-assembly long-chained carboxylic acids and phosphonic acids on thin aluminum oxide surfaces and investigated their dielectric properties in capacitors and low-voltage organic thin-film transistors. Phosphonic acid anchor groups tend to substitute carboxylic acid molecules on aluminum oxide surfaces and thus allow the formation of mixed or fully exchanged monolayers. With different alkyl chain substituents (n-alkyl or fluorinated alkyl chains), the exchange reaction can be monitored as a function of time by static contact angle measurements. The threshold voltage in α,α′-dihexyl-sexithiophene thin-film transistors composed of such mixed layer dielectrics correlates with the exchange progress and can be tuned from negative to positive values or vice versa depending on the dipole moment of the alkyl chain substituents. The change in the dipole moment with increasing exchange time also shifts the capacitance of these devices. The rate constants for exchange reactions determined by the time-dependent shift of static contact angle, threshold voltage, and capacitance exhibit virtually the same value thus proving the exchange kinetics to be highly controllable. In general, the exchange approach is a powerful tool in interface engineering, displaying a great potential for tailoring of device characteristics.